1999
DOI: 10.1046/j.1365-2761.1999.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water quality and temperature on adhesion of high and low virulence Flavobacterium columnare strains to isolated gill arches

Abstract: The ability of Flavobacterium columnare (Flexibacter columnaris) to attach to the gills of common carp, Cyprinus carpio L., was evaluated using a gill perfusion model. A comparison between a high and a low virulence strain of F. columnare was made and evaluated in comparison to results obtained previously with an in vivo model. The ion composition of the water of the organ bath in which the gills were suspended was varied and the influence on adhesion processes assessed. Experiments were carried out to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 20 publications
3
80
0
2
Order By: Relevance
“…Although the growth of the bacteria increases at elevated temperatures, this is not the only factor increasing fish mortality at high temperatures during columnaris infection. At higher temperatures the transmission of the pathogen and mortality caused by the disease are higher (Suomalainen et al 2005a), and the adhesion of the pathogen in fish tissues has also been shown to increase at elevated temperatures (Decostere et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the growth of the bacteria increases at elevated temperatures, this is not the only factor increasing fish mortality at high temperatures during columnaris infection. At higher temperatures the transmission of the pathogen and mortality caused by the disease are higher (Suomalainen et al 2005a), and the adhesion of the pathogen in fish tissues has also been shown to increase at elevated temperatures (Decostere et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although the growth of the bacteria increases at elevated temperatures, this is not the only factor increasing fish mortality at high temperatures during columnaris infection. At higher temperatures the transmission of the pathogen and mortality caused by the disease are higher (Suomalainen et al 2005a), and the adhesion of the pathogen in fish tissues has also been shown to increase at elevated temperatures (Decostere et al 1999).The Ministry of Agriculture and Forestry in Finland recommends tetracycline for treatment of columnaris disease, but the use of florfenicol is accepted as an alternative antibiotic if tetracycline-resistant strains should occur. Even though the Finnish Flavobacterium columnare strains seem to be sensitive to tetracycline at the moment, the development of resistance can happen.…”
mentioning
confidence: 99%
“…For example, the polysaccharide capsule (slime layer) of Flavobacterium columnare plays an important role in the adhesion to the gill tissue that causes columnaris disease in marine fish (Decostere et al, 1999). Azospirillum, the free-living N 2 -fixing rhizobacterium, possesses the capacity to aggregate and flocculate.…”
Section: Introductionmentioning
confidence: 99%
“…The most probable explanation for this mortality is impaired quality of the water in tanks caused by compromised function of biological filters which resulted in a higher concentration of nitrites (1.73 ± 1.65 mg/l for T1). Even if these parameters might lead to stressing and weakening of fish (Carballo and Munoz 1991) and, consequently, to a heightened sensitivity to bacterial (Decostere et al 1999) or viral (Inendino et al 2005) infections, nested PCR did not reveal the presence of viral DNA in samples taken during the secondary challenge. Therefore, even though stone loach and sterbel were found to be CyHV-3 DNA-positive at the end of the primary challenge (on the 30 th dpi), the fact that fish that were removed from the infected tanks (E1 and E2) on the 15 th dpi (sampled or transferred to the transmission tanks and sampled after a further 30 days) were CyHV-3-negative could suggest that 15 days of cohabitation with KHV-infected fish is not enough for infection of stone loach and sterbel.…”
Section: Discussionmentioning
confidence: 99%